Weight bias internalization in a commercial weight management sample: prevalence and correlates. (11th July 2019) - Pearl, R. L.; Himmelstein, M. S.; Puhl, R. M.; Wadden, T. A.; Wojtanowski, A. C.; Foster, G. D.
Summary: Objective: Weight bias internalization (WBI) is associated with poor weight‐related health. The purpose of this study was to identify the prevalence and correlates of WBI in a large sample of adults in a commercial weight management programme. Methods: WW (the new Weight Watchers) members participated in an online survey. Participants ( N = 18, 769) completed the 10‐item Weight Bias Internalization Scale – Modified (WBIS‐M) and the Weight Self‐Stigma Questionnaire (WSSQ). Participants reported details about weight‐stigmatizing experiences, including the onset, frequency and distress, and interpersonal sources of weight stigma. Participants self‐reported their demographics, weight history, and height and weight (to compute body mass index [BMI]). Results: Weight bias internalization was relatively high compared with the general population (mean WBIS‐M score = 4.3 ± 1.4; mean WSSQ total score = 35.2 ± 9.7). WBI was higher among participants who were female, younger and had higher BMIs ( p < 0.001) and lower among those who were Black and were widowed or had a romantic partner ( p < 0.001). Onset of weight stigma in childhood and young adulthood, and recent distress due to weight stigma, predicted higher WBI. Extended family and school sources of weight stigma had weaker associations with WBI than did other interpersonal sources. Conclusions: Weight bias was internalized by a significant proportion of adults enrolled in a commercial weight management programme. A phenotype of WBI includes demographic characteristics and the timing and sources of weight stigma.